2021
DOI: 10.1126/sciadv.abk2200
|View full text |Cite
|
Sign up to set email alerts
|

Delta glutamate receptors are functional glycine- and ᴅ-serine–gated cation channels in situ

Abstract: The synaptic proteins cerebellin-1 and neurexin-1β permit ion channel activity in delta subtype of ionotropic glutamate receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 46 publications
0
22
1
Order By: Relevance
“…This result suggests that the CTD of GluN1/GluN2A receptors is necessary for their mechanical activation by gentle suction. This observation may indicate that the CTD is necessary to transmit force from the cytoskeleton to the gate; alternatively, it may indicate that the energy provided by suction, transmitted by some other unknown mechanism, is sufficient to gate the channel only when the tethering of the CTD to intracellular structures provides a certain threshold of rigidity to the observed receptor, a case demonstrated recently for GluD receptors (Carrillo, Gonzalez, Berka, & Jayaraman, 2021).…”
Section: Stretch-gated Nmda Currents Require the Receptor's Carboxyl ...mentioning
confidence: 76%
See 1 more Smart Citation
“…This result suggests that the CTD of GluN1/GluN2A receptors is necessary for their mechanical activation by gentle suction. This observation may indicate that the CTD is necessary to transmit force from the cytoskeleton to the gate; alternatively, it may indicate that the energy provided by suction, transmitted by some other unknown mechanism, is sufficient to gate the channel only when the tethering of the CTD to intracellular structures provides a certain threshold of rigidity to the observed receptor, a case demonstrated recently for GluD receptors (Carrillo, Gonzalez, Berka, & Jayaraman, 2021).…”
Section: Stretch-gated Nmda Currents Require the Receptor's Carboxyl ...mentioning
confidence: 76%
“…In addition, mechanical constraints imposed by interaction with cellular and/or intracellular structures, even if not serving as mechanical transducers, may serve to limit the receptor's conformational freedom and thus facilitate or oppose their mechanical activation. This scenario was recently described for GluD receptors, which can be gated by neurotransmitter only when their N-terminal domains are reinforced by interactions with trans-cellular proteins (Carrillo et al, 2021). Therefore, although the CTD appears necessary for mechanical gating of NMDA receptors, it remains to be determined whether this is a case of force-from filament mechanism, or the CTD simply stabilizes the molecule in a mechano-sensitive conformation.…”
Section: Discussionmentioning
confidence: 95%
“…The need for these non‐swapped receptors to be structurally stabilized was very recently demonstrated by Carrillo et al . [7], who elegantly showed that GluD2 receptors can be directly activated by glycine and D‐serine in situ when bound to cerebellin 1 and neurexin‐1β. It would therefore be interesting to see similar in situ studies on GluD1.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a GluD2 A654T point mutation in lurcher mice (GluD2 lurcher mutant, GluD2‐Lc) causes spontaneous channel activity [4] that is reduced by D‐serine application [5], most likely by a desensitization‐like mechanism [6]. The picture has very recently changed due to the work of Carrillo et al ., who showed that GluD2 receptors form cation‐gated ion channels in situ when bound to cerebellin 1 and neurexin‐1β, which act to compress the N‐terminal domain, and that glycine and D‐serine under those conditions function as an agonist at GluD2 [7].…”
Section: Introductionmentioning
confidence: 99%
“…The glutamate delta receptors GluD1 (encoded by the GRID1 gene) and GluD2 ( GRID2 gene) belong to the family of ionotropic glutamate receptors (iGluRs), which consist in homo- or heterotetrameric arrangements of subunits, and play key roles in synaptic transmission and plasticity (Traynelis et al ., 2010; Yuzaki and Aricescu, 2017; Burada et al ., 2021). GluDs do not bind glutamate but, instead, the binding of cerebellin and D-serine on distinct extracellular domains cooperatively gate GluD ion channels, whose opening is alternatively triggered by activation of Gq-coupled metabotropic glutamate receptors (mGlu1/5), or α1-adrenergic receptors (Ady et al ., 2014; Benamer et al ., 2018; Gantz et al ., 2020; Carrillo et al ., 2021). The binding of these ligands also triggers or modulates metabotropic signals, cerebellin additionally enabling postsynaptic GluDs to participate in excitatory synapse formation/stabilization via attachment with presynaptic neurexin (Yuzaki and Aricescu, 2017; Tao et al ., 2018; Andrews and Dravid, 2021; Burada et al ., 2021; Dai et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%